Impact of single dose photons and carbon ions on perfusion and vascular permeability: a dynamic contrast-enhanced MRI pilot study in the anaplastic rat prostate tumor R3327-AT1 - Bendinger, Alina L.; Seyler, Lisa; Saager, Maria; Debus, Charlotte; Peschke, Peter; Komljenovic, Dorde; Debus, Jürgen; Peter, Jörg; Floca, Ralf; Karger, Christian; Glowa, Christin (Radiation research, 2019)
We collected initial quantitative information on the effects of high-dose carbon (12C) ions compared to photons on vascular damage in anaplastic rat prostate tumors, with the goal of elucidating differences in response to high-LET radiation, using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Syngeneic R3327-AT1 rat prostate tumors received a single dose of either 16 or 37 Gy 12C ions or 37 or 85 Gy 6 MV photons (iso-absorbed and iso-effective doses, respectively). The animals underwent DCE-MRI prior to, and on days 3, 7, 14 and 21 postirradiation. The extended Tofts model was used for pharmacokinetic analysis. At day 21, tumors were dissected and histologically examined. The results of this work showed the following: 1. 12C ions led to stronger vascular changes compared to photons, independent of dose; 2. Tumor growth was comparable for all radiation doses and modalities until day 21; 3. Nonirradiated, rapidly growing control tumors showed a decrease in all pharmacokinetic parameters (area under the curve, Ktrans, ve, vp) over time; 4. 12C-ion-irradiated tumors showed an earlier increase in area under the curve and Ktrans than photon-irradiated tumors; 5. 12C-ion irradiation resulted in more homogeneous parameter maps and histology compared to photons; and 6. 12C-ion irradiation led to an increased microvascular density and decreased proliferation activity in a largely dose-independent manner compared to photons. Postirradiation changes related to 12C ions and photons were detected using DCE-MRI, and correlated with histological parameters in an anaplastic experimental prostate tumor. In summary, this pilot study demonstrated that exposure to 12C ions increased the perfusion and/or permeability faster and led to larger changes in DCE-MRI parameters resulting in increased vessel density and presumably less hypoxia at the end of the observation period when compared to photons. Within this study no differences were found between curative and sub-curative doses in either modality.